OPTIMIZATION OF GOVERNMENT: TNI AND POLRI ROLES THROUGH GOOD GOVERNANCE CONCEPT IN COUNTERING RADICALISM ISSUES IN INDONESIA - Tri Adianto; Tihas Citra Buwana; Marcellinus Dicky Pradhana; Aris Sarjito (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Radicalism has become a real threat faced by all countries in the world, including Indonesia. This condition occurs because radicalism is the origin ideology of terrorism which has been confirmed as an extraordinary crime for the world. So, the Indonesian government needs to pay special attention to counter the radicalism issue which is now growing rapidly in Indonesia. This article was written to analyze the Government, the Indonesian National Armed Forces (TNI), and the Indonesian National Police (Polri) roles in countering radicalism issues in Indonesia through good governance concept. This article is written based on the result of phenomenology research used literature study approach of various literature that is relevant to the research topic. Based on the study, the results show that the countering process of radicalism issues conducted by the government of the Republic of Indonesia has not been well managed, because there is no strong legal basis concerning radicalism in Indonesia. Additionally, the weak synergy between the TNI and the Polri, which is tasked to countering radicalism issues, is also become an obstacle for eradicate radicalism issues in Indonesia. Therefore, optimizing the role of the Government, TNI, and Polri are needed by prevention, mapping, detention, and contra radicalism actions. On the other hand, those three parties must strengthen their synergy and cooperative in performed their roles in maintaining public security and national security from the dangers of radicalism.